UMP receives MPV from Perodua - Mimi Rabita, Abdul Wahit (2022)
PEKAN, 28 July 2022 – Universiti Malaysia Pahang (UMP) received a multi-purpose vehicle (MPV) Perodua Alza donated by Perusahaan Otomobil Kedua Sdn. Bhd. (Perodua). The contribution symbolises the appreciation from Perodua to UMP as the first university to receive Sijil Bersih from the National Audit Department for ten consecutive years since 2012.